Nutrition for improved sports performance. Current issues on ergogenic aids - Clarkson, P. M. (Sports Medicine, 1996)
Several nutritional modifications have been used by athletes to improve performance. Recent attention has focused on high fat diets, branched-chain amino acids, creatine, carnitine, bicarbonate and phosphate loading, and caffeine. Of these, only caffeine, which is present in food but has no known nutritional value, appears on the list of substances banned by the International Olympic Committee (IOC). While there is a theoretical basis for each of these diet manipulations to enhance performance, there are insufficient data to state unequivocally that high fat diets, branched-chain amino acids, carnitine or phosphate loading are effective. Caffeine has been found to enhance endurance performance, while creatine and bicarbonate loading were generally found to benefit short term strenuous exercise. Acute ingestion of these diet manipulations appears safe, although some, like caffeine and bicarbonate, can cause gastrointestinal disturbances or other problems in certain individuals. Long term use of high fat diets may have negative consequences on health. The safety of long term use of these diet manipulations has not been established.